2015
DOI: 10.1097/nna.0000000000000220
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Instrument to Measure Civil and Uncivil Behaviors in the Hospital Clinical Environment

Abstract: This study has produced a valid and reliable survey instrument to measure the perception of civil and noncivil behaviors on the part of clinical nurses as rated by NSs in hospital clinical settings. The use of this instrument will be beneficial to nurse executives in measuring these perceptions in their clinical settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 0 publications
0
10
0
2
Order By: Relevance
“…All 38 of the studies were reviewed for systems‐level evidence, which identified, explained, and evaluated workplace incivility among healthcare workers, especially among nurses, as an international concern in health systems. The interconnectedness of the system layers are bound by productivity policies, reimbursement, and accrediting agency standards . Increasing work productivity assessments can be used to balance budgets.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All 38 of the studies were reviewed for systems‐level evidence, which identified, explained, and evaluated workplace incivility among healthcare workers, especially among nurses, as an international concern in health systems. The interconnectedness of the system layers are bound by productivity policies, reimbursement, and accrediting agency standards . Increasing work productivity assessments can be used to balance budgets.…”
Section: Resultsmentioning
confidence: 99%
“…A second framework for reduction of incivility, which can be applied to both practice and academic settings recommends that incivility be acknowledged as a problem and simulation used as an educational strategy to promote practice . Tecza et al . developed a survey to assist nurse leaders in developing evidence‐based interventions to combat incivility, leading to healthier work environments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reliability testing of the NSPCUB revealed a Cronbach's alpha for the entire instrument of .927 indicating high reliability of measuring incivility in the CLE. [14] The Cronbach's alpha for this study was determined to be .937. Few studies have utilized this tool.…”
Section: Introductionmentioning
confidence: 98%
“…[13] The Nursing Student Perception of Civil and Uncivil Behaviors (NSPCUB) tool was developed in 2015. [14] The NSPCUB is a 12 item questionnaire designed to measure the nursing student experience. It has a 4-point Likert scale ranging from "strongly disagree" to "strongly agree".…”
Section: Introductionmentioning
confidence: 99%